Empirical analysis of values on interactive advertisement aimed at a teenage audience - Belinda de Frutos-Torres; María Sánchez-Valle; Tamara Vázquez-Barrio (Communication & Society (Formerly Comunicación y Sociedad), 2012)
This paper aims to examine the values reflected in Internet advertising. To achieve this, a content analysis which identifies the values reflected by advertisements on web sites targeting teenagers, has been performed. Analysis results show that the most frequent values are related to transgression, adventure, materialism, competitiveness and power. The study also reveals a relationship between the target audience and the type of values. Campaigns aimed at youth have a significant presence of transgression, adventure, materialism, power, competitiveness and personal success values, while campaigns aimed at both targets (adults and youth simultaneously) have a significant presence of normative values.